(untitled) (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2017)
Teacher is an urgent and determinative factor in education. it has a central and determinative position in the learning process. the education society prosecutesÂ in the improvement of the teacher quality. it could not postponed anylonger, as what implicitly shown at law number 20 of 2003 on national education system, law number 14 of 2005 on teacher and lecturer, and government regulation number 19 of 2005 on national standard of education. furthermore, the implementation of competence based curriculum (KB), and then Kurikulum Tingkat Satuan Pendidikan (KTSP), brings on educators to have enough competence.